In pursuit of a better world: crop improvement and the CGIAR. (22nd May 2021) - Kholová, Jana; Urban, Milan Oldřich; Cock, James; Arcos, Jairo; Arnaud, Elizabeth; Aytekin, Destan; Azevedo, Vania; Barnes, Andrew P; Ceccarelli, Salvatore; Chavarriaga, Paul; Cobb, Joshua N; Connor, David; et al.
Abstract: The CGIAR crop improvement (CI) programs, unlike commercial CI programs, which are mainly geared to profit though meeting farmers' needs, are charged with meeting multiple objectives with target populations that include both farmers and the community at large. We compiled the opinions from >30 experts in the private and public sector on key strategies, methodologies, and activities that could the help CGIAR meet the challenges of providing farmers with improved varieties while simultaneously meeting the goals of: (i) nutrition, health, and food security; (ii) poverty reduction, livelihoods, and jobs; (iii) gender equality, youth, and inclusion; (iv) climate adaptation and mitigation; and (v) environmental health and biodiversity. We review the crop improvement processes starting with crop choice, moving through to breeding objectives, production of potential new varieties, selection, and finally adoption by farmers. The importance of multidisciplinary teams working towards common objectives is stressed as a key factor to success. The role of the distinct disciplines, actors, and their interactions throughout the process from crop choice through to adoption by farmers is discussed and illustrated. Abstract : This document arose from the urgent need to join forces (across nations and research disciplines) and stand together to improve the prospects for the most vulnerable population on the globe whose well-being depends on agricultural production. Here, we learn from the past, and draft future strategic guidelines that will facilitate efforts of the CGIAR institutions (https://www.cgiar.org/ ) to enhance the livelihoods of the less privileged through crop improvement.